2017
DOI: 10.1038/srep46477
|View full text |Cite
|
Sign up to set email alerts
|

Novel SUMO-Protease SENP7S Regulates β-catenin Signaling and Mammary Epithelial Cell Transformation

Abstract: SUMO post-translational modification of proteins or SUMOylation ensures normal cell function. Disruption of SUMO dynamics prompts various pathophysiological conditions, including cancer. The burden of deSUMOylating the large SUMO-proteome rests on 6 full-length mammalian SUMO-proteases or SENP. While multiple SENP isoforms exist, the function of these isoforms remains undefined. We now delineate the biological role of a novel SENP7 isoform SENP7S in mammary epithelial cells. SENP7S is the predominant SENP tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
8
16
0
Order By: Relevance
“…Finally, the decreasing gradient of SUMOylation in the adrenal cortex also suggests its possible involvement in the establishment and/or maintenance of cortical zonation. Increased SUMOylation consecutive to depletion of SENP1/2/7 proteins was reported in various models to activate the WNT/b-catenin pathway by increasing b-catenin stability (62,63) and by promoting its nuclear translocation (64,65). The ability of SUMOylation to activate the WNT pathway is likely to explain the intense staining observed in zG.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, the decreasing gradient of SUMOylation in the adrenal cortex also suggests its possible involvement in the establishment and/or maintenance of cortical zonation. Increased SUMOylation consecutive to depletion of SENP1/2/7 proteins was reported in various models to activate the WNT/b-catenin pathway by increasing b-catenin stability (62,63) and by promoting its nuclear translocation (64,65). The ability of SUMOylation to activate the WNT pathway is likely to explain the intense staining observed in zG.…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, SENP7L protein is elevated in invasive carcinoma. [28] Previously, it was showed that SENP7 is required for chromatin relaxation in response to DNA damage, for homologous recombination repair and for cellular resistance to DNA-damaging agents. [29] It was also demonstrated that targeted knockdown of the SENP7 gene transcript NM_001077203.2 alters Wnt-activated β-catenin signaling in a sarcoma cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that deletion of SENP7S can directly enhance the tumorigenicity of MCF-10-2A cells. Mechanistically, SENP7 loss enhances the SUMOylation of β-catenin, and SUMOylated β-catenin is transported to the nucleus and promotes the transcription of oncogenes, including c-Myc, cyclin D, and Aurora kinase, ultimately promoting metastasis and invasion of breast cancer ( 38 ).…”
Section: Senp Family Members and Breast Cancermentioning
confidence: 99%